All-trans retinoic acid inhibits lipopolysaccharide-induced inflammatory responses in bovine adipocytes via TGFβ1/Smad3 signaling pathway - Xu, Qiushi; Jia, Hongdou; Ma, Li; Liu, Guowen; Xu, Chuang; Li, Ying; Li, Xinwei; Li, Xiaobing (BMC veterinary research, 2019)
Dairy cows with metabolic disorder in peripartal period display high inflammatory levels. Adipose tissue is a major endocrine organ, which is closely related to systemic inflammation. Retinoic acid (RA), an active metabolite of vitamin A, has shown potential therapeutic immunomodulatory properties. The objective of the study was to examine the effect of all-trans-RA (ATRA), the biologically most active metabolite of vitamin A, on lipopolysaccharide (LPS)-induced bovine adipocytes inflammatory responses and elucidate the underlying mechanisms. Primary cultured bovine adipocytes were treated with ATRA in the presence or absence of LPS. The treated cells were examined for the inflammatory responses and the activity of transforming growth factor beta 1 (TGFβ1) /Smad3 signaling pathway. LPS treatment significantly decreased the expression levels of TGFβ1/Smad3 components and increased the content of pro-inflammatory cytokines. Treatment with ATRA could over-activate TGFβ1/Smad3 signaling pathway in bovine adipocytes and reversed the over-production of pro-inflammatory cytokines and inhibition of anti-inflammatory cytokines induced by LPS. Importantly, inhibition of TGFβ1/Smad3 signaling diminished the effects of ATRA on suppressing the proinflammatory responses induced by LPS. Furthermore, activation of TGFβ1/Smad3 signaling further extended the effects of ATRA on suppressing the proinflammatory responses on LPS stimulation. In conclusion, ATRA stimulates TGFβ1/Smad3 signaling pathway and further suppresses bovine adipocytes inflammatory responses induced by LPS.